One-step synthesis of mesoporous Pt–Nb2O5 nanocomposites with enhanced photocatalytic hydrogen production activity. Issue 99 (11th October 2016) - Zhang, Hualei; Lin, Qianying; Ning, Shangbo; Zhou, Yangen; Lin, Huaxiang; Long, Jinlin; Zhang, Zizhong; Wang, Xuxu
Abstract : The loading of uniform and smaller sized Pt particles onto Nb2 O5 was beneficial to interfacial transfer and produced more radicals. Abstract : Mesoporous Pt–Nb2 O5 photocatalysts with high photocatalytic hydrogen production activity were synthesized by a one-step method. The mesoporous structure of the as-made samples was characterized by X-ray diffraction, N2 adsorption–desorption isotherms and transmission electron microscopy. Pt–Nb2 O5 exhibited higher hydrogen production activity than pure Nb2 O5 and 0.8-Pt–D–M–Nb exhibited the best photocatalytic activity. In addition, Pt–Nb2 O5 synthesized by a one-step method exhibited higher photocatalytic hydrogen production activity than that prepared by an incipient wetness impregnation method; 0.8-Pt–D–M–Nb exhibits a H2 evolution rate of 9.79 mmol h −1 g −1, while 0.8-Pt–I–M–Nb2 O5 exhibits a H2 evolution rate of 7.73 mmol h −1 g −1 . The enhanced photocatalytic activity of Pt–Nb2 O5 was predominantly attributed to the efficient separation of photoinduced electrons and holes.